Nosocomial Outbreak of Carbapenemase-Producing Proteus mirabilis With Two Novel Salmonella Genomic Island 1 Variants Carrying Different blaNDM–1 Gene Copies in China - Yang, Lang; He, Hong; Chen, Qichao; Wang, Kaiying; Lin, Yanfeng; Li, Peihan; Li, Jinhui; Liu, Xiong; Jia, Leili; Song, Hongbin; Li, Peng (Frontiers in Microbiology, 2022)
NDM-1-producing multidrug-resistant Proteus mirabilis brings formidable clinical challenges. We report a nosocomial outbreak of carbapenem-resistant P. mirabilis in China. Six P. mirabilis strains collected in the same ward showed close phylogenetic relatedness, indicating clonal expansion. Illumina and MinION sequencing revealed that three isolates harbored a novel Salmonella genomic island 1 carrying a blaNDM-1 gene (SGI1-1NDM), while three other isolates showed elevated imipenem resistance and carried a similar SGI1 but with two blaNDM-1 gene copies (SGI1-2NDM). Four new single nucleotide mutations were present in the genomes of the two-blaNDM-1-harboring isolates, indicating later emergence of the SGI1-2NDM structure. Passage experiments indicated that both SGI variants were stably persistent in this clone without blaNDM-1 copy number changes. This study characterizes two novel blaNDM-1-harboring SGI1 variants in P. mirabilis and provides a new insight into resistance gene copy number variation in bacteria.